DETERMINAN TINGKAT PENGANGGURAN DAN KEMISKINAN DI KAWASAN SARBAGITA - Budiarto, Yogi Pratama; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Sustainable Development Goals (SDG’s) is poverty alleviation at all levels. Government of Bali in 2009 launched a program which is an elite area, hereinafter referred to as the Sarbagita. In the Sarbagita region, the unemployment and poverty on last two years in several regions have increased. The research objectives to be achieved, (1) To analyze the effect of capital expenditure, minimum wages, on the unemployment rate in the Sarbagita region. (2) To analyze the effect of capital expenditure, minimum wages, on the number of poor people in the Sarbagita region. (3) To analyze the effect of capital expenditure and minimum wages, on the number of poor people through the unemployment rate in the Sarbagita region. The analysis technique uses path analysis. The results of the study are (1) capital expenditure and minimum wages have a negative (significant) effect on the unemployment rate in the Sarbagita region. (2) capital expenditure, minimum wage, and unemployment rate have a negative (significant) effect on poverty levels in the Sarbagita region. (3) Capital expenditure and minimum wages in the Sarbagita region indirectly affect poverty levels through the unemployment rate.   Keywords: capital expenditure, minimum wage, unemployment rate, unemployment rate